BODY AND URBAN VIOLENCE: AN ESSAY ABOUT THE PRACTICE OF MARTIAL ARTS IN THE CONTEXT OF RIODE JANEIRO CITY. (Fiep Bulletin - online, 2015)
One of the most serious problems related to Brazilian society is the urban violence with many sides and many forms; it invades our social spaces and modifies people's way of life. A phenomenon that confirms this picture is the existence of “gangs of young people”. They are generally formed by adults and adolescents from the highest classes of the society united to practice the most violent acts against people and properties. News from the media says that the phenomenon has something in common with young people's behavior and one of these behaviors is the systematic practice of martial arts. So, this study aims to investigate the forms of social interaction of the practicers of martial arts. From this perspective, data will be collected so that urban violence may be mapped through the analysis of police archives and wit a structured interview with these practicers to verify if there is a relation between these two variables, besides observing in loco to see if there is a unification between the instructor and the practicers in terms of language and behavior. We understand that data collection will allow the structure of intervention proposals based on interdisciplinary strategies, principally in sociological and psychological areas.
Keywords: urban violence; martial arts; media